El clima organizacional y su influencia en el desempeño laboral de los trabajadores de la Municipalidad Provincial de Sánchez Carrión - 2016 - Rodríguez Corales, Cinthya Lizbeth (2017)
The present research aims to determine if there is a direct relationship between the Organizational Climate and Work Performance of the workers of the Municipality of Sánchez Carrión. The research question is related to the following question: How does the organizational climate influence the work performance of the workers of the Provincial Municipality of Sánchez Carrión in 2016, whose hypothesis is: A good organizational climate improves work performance of the workers of the Provincial Municipality of Sánchez Carrión in 2016, highlighting as study variables: Independent Variable: Organizational Climate; And the variable Dependent: Labor Performance. We used descriptive cross-sectional research design as well as inductive methods; Analytical, statistical and research technique of data collection, such as the survey. Through the studies carried out in the Municipality of Sánchez Carrión, it can be concluded that: Employees of the Provincial Municipality of Sánchez Carrión perceive the organizational climate on a regular basis, this being a key indication for work performance. It does not have a training plan, employee evaluation, motivational talks. There is a lack of motivation among workers because of the lack of recognition of their work by the managers. The communication systems that are currently applied in the company are formal and the hierarchical style is maintained, which prevents the strengthening of the ties between managers and workers. Failure to foster teamwork leads to a lack of fellowship and participation in business activities, which ultimately impacts on the lack of organizational commitment.